Investigação das propriedades fotofísicas e estudo da interação com biomoléculas de porfirinas meso-substituídas em posição meta contendo complexos de PdII, PtII e RuII - Silveira, Carolina Hahn da (2022)
This work aimed at the synthesis of porphyrins: meso-tetra(3-pyridyl)porphyrin (3-H2TPyP), meso-tetra [(3- pyridyl)-chlor-(2,2'-bipyridyl)-palladium(II) ]porphyrin (3-Pd(bpy)TPyP), meso-tetra[(3-pyridyl)-chloro-(1,10- phenanthroline)-palladium(II)]porphyrin (3-Pd(phen)TPyP), meso-tetra[(3-pyridyl)-chloro-(2,2'-bipyridyl)- platinum(II)]porphyrin (3-Pt(bpy)TPyP), meso-tetra[(3-pyridyl)-chloro-(1,10-phenanthroline)-platinum(II)] porphyrin (3-Pt(phen)TPyP), meso-tetra[(3-pyridyl)-chloro-bis(2,2'-bipyridyl)-ruthenium(II)]porphyrin (3- Ru(bpy)TPyP) and meso-tetra[(3-pyridyl)-chloro-bis(1,10-phenanthroline)-ruthenium(II)]porphyrin (3- Ru(phen)TPyP). The compounds were characterized by elemental analysis of CHN%, electronic spectroscopy in the ultraviolet-visible and infrared regions, fluorescence emission spectroscopy. In addition, aggregation tests in solution were performed, its photophysical properties, such as photostability and singlet oxygen generation, were investigated. The interactions of these compounds with the biomolecule were also investigated, through interactive studies with calf thymus deoxyribonucleic acid (CT-DNA) and studies with human serum albumin (HSA). To analyze and understand the interactions of these compounds, experiments were performed via UV-Vis spectroscopy. The compounds showed good photo-stability, in the studied light irradiation range, but low quantum yields of singlet oxygen. The assays of interactions with CT-DNA showed results with low values for binding constants (Kb), they also presented low to moderate values of Stern-Volmer suppression constants (Ksv) in the assays of competitors with different dyes, on the other hand, the Gibbs free energy values suggest spontaneous processes. In addition, docking molecular suggests that the greatest interaction is through the smallest groove in the DNA. In relation to the interaction assays with the HSA protein, the constants of Ksv and Ka were in the order of 104 L mol−1 and with the help of theoretical calculations, it was identified that the preference for their interaction is the IB subdomain.